Respuesta :

Answer:

x=−1.36665

Step-by-step explanation:

Let's solve your equation step-by-step.

73x+1=6x−2

Solve Exponent.

73x+1=6x−2

log(73x+1)=log(6x−2)(Take log of both sides)

(3x+1)*(log(7))=(x−2)*(log(6))

3x+1=(

log(6)

log(7)

)*(x−2)

3x+1=0.920782*(x−2)

3x+1=0.920782x−1.841564(Simplify both sides of the equation)

3x+1−0.920782x=0.920782x−1.841564−0.920782x(Subtract 0.920782x from both sides)

2.079218x+1=−1.841564

2.079218x+1−1=−1.841564−1(Subtract 1 from both sides)

2.079218x=−2.841564

2.079218x

2.079218

=

−2.841564

2.079218

(Divide both sides by 2.079218)

x=−1.36665